No place like home : locations of Heimat in German cinema - Von Moltke, Johannes, 1966- (Berkeley : University of California Press, 2005)
This is the first comprehensive account of Germany's most enduring film genre, the Heimatfilm, which has offered idyllic variations on the idea that "there is no place like home" since cinema's early days. Charting the development of this popular genre over the course of a century in a work informed by film studies, cultural history, and social theory, Johannes von Moltke focuses in particular on its heyday in the 1950s, a period that has been little studied.
List of Illustrations; Acknowledgments; Introduction: Locating Heimat; 1. Evergreens: The Place of Heimat in German Film History; 2. Therapeutic Topographies: From Ludwig Ganghofer to the Nazi Heimatfilm; 3. Launching the Heimatfilmwelle: From the Trümmerfilm to Grün ist die Heide; 4. Heimat/Horror/History: Rosen blühen auf dem Heidegrab; 5. Nostalgic Modernization: Locating Home in the Economic Miracle; 6. Expellees, Emigrants, Exiles: Spectacles of Displacement; 7. Collectivizing the Local: DEFA and the Question of Heimat in the 1950s.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
English.
eBooks on EBSCOhost
Keywords: Heimatfilme -- History and criticism; Motion pictures -- Germany -- History; Heimatfilm -- Histoire et critique; Cinéma -- Allemagne -- Histoire; PERFORMING ARTS -- Film & Video -- Reference; PERFORMING ARTS -- Film & Video -- General; Heimatfilme; Motion pictures; Germany; Motion pictures; Criticism, interpretation, etc; History; Motion pictures; Films